Materiality and the Constitution of Images (KULT_online, 2013)
This collection of articles edited by Marcel Finke and Mark A. Halawa deals with the problem of the materiality of images. Fifteen theoretical and historical contributions tackle the complex task of acknowledging the role that the material plays in the semiotic and aesthetic construction of images. The focus is on art from the nineteenth century onwards, and digital images are awarded particular prominence. While a presentation of points of emphasis and results in the introduction would have made the volume more reader-friendly, it provides a challenging starting-point for further research on the issue.